Dynamically Stable Sets in Infinite Strategy Spaces. - Norman, T (Elsevier, 2008)
Evolutionary game theory has largely focused on finite games. Dynamic stability is harder to attain in infinite strategy spaces; Bomze [Bomze, I., 1990. Dynamical aspects of evolutionary stability. Monatsh. Math. 110, 189-206] and Oechssler and Riedel [Oechssler, J., Riedel, F., 2001. Evolutionary dynamics on infinite strategy spaces. Econ. Theory 17, 141-162] provide conditions for the stability of rest points under the replicator dynamics. Here, conditions are given for the stability of sets of strategies under this process.